Pollinosis and all‐cause mortality among middle‐aged and elderly Japanese: a population‐based cohort study. Issue 8 (3rd May 2016) - Konishi, S.; Ng, C. F. S.; Stickley, A.; Watanabe, C.
Summary: Background: Having an allergic disease may have health implications beyond those more commonly associated with allergy given that previous epidemiological studies have suggested that both atopy and allergy are linked to mortality. More viable immune functioning among the elderly, as indicated by the presence of an allergic disease, might therefore be associated with differences in all‐cause mortality. Objective: Using data from a Japanese cohort, this study examined whether having pollinosis (a form of allergic rhinitis) in a follow‐up survey could predict all‐cause and cause‐specific mortality. Methods: Data came from the Komo‐Ise cohort, which at its 1993 baseline recruited residents aged 40–69 years from two areas in Gunma prefecture, Japan. The current study used information on pollinosis that was obtained from the follow‐up survey in 2000. Mortality and migration data were obtained throughout the follow‐up period up to December 2008. Proportional hazard models were used to examine the relation between pollinosis and mortality. Results: At the 2000 follow‐up survey, 12% (1088 of 8796) of respondents reported that they had pollinosis symptoms in the past 12 months. During the 76 186 person‐years of follow‐up, 748 died from all causes. Among these, there were 37 external, 208 cardiovascular, 74 respiratory, and 329 neoplasm deaths. After adjusting for potential confounders, pollinosis was associated with significantly lower all‐cause [hazard ratio 0.57 (95% confidence interval = 0.38–0.87)] and neoplasms mortality [hazard ratio 0.48 (95% confidence interval = 0.26–0.92)]. Conclusions and clinical relevance: Having an allergic disease (pollinosis) at an older age may be indicative of more viable immune functioning and be protective against certain causes of death. Further research is needed to determine the possible mechanisms underlying the association between pollinosis and mortality.